The Effects of Entrepreneurial Leadership, Recruitment and Innovation on Learning Organization and Organizational Performance of Four Star Hotels in East Java - Mohammad Soleh; Ida Aju Brahmasari; Ida Aju Brahma Ratih (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: The purpose of this study is to analyze the effects of entrepreneurial leadership, recruitment and innovation to learning organization and organizational performance at four-star hotels in East Java. Design/methodology/approach: The research design used an explanatory research approach, with the research sample being the leadership or management of a four-star hotel in East Java, with a total sample of 71 respondents. The analytical technique used is SEM-PLS (SEM-Partial Least Square). Findings: The results of the analysis conclude that there are five accepted hypotheses, namely (1) entrepreneurial leadership has a positive and significant effects on learning organizations, (2) recruitment has a positive and significant effects on learning organizations, (3) innovation has a positive and significant effects on learning organizations, (4) innovation has a positive and significant effects on organizational performance, (5) learning organization has a positive and significant effects on organizational performance. Research limitation/implications: The rest, there are two rejected hypotheses, namely (1) entrepreneurial leadership has no significant effects on organizational performance, and (2) recruitment has no significant effects on organizational performance. Originality/value: This Paper is original Paper Type: Research paper